Sporotrichosis in an unusual location - Case report - Brisa Dondoni Reis; Fernanda Oliveira Cobucci; Luciana Helena Zacaron; Antonio Macedo D'Acri; Ricardo Barbosa Lima; Carlos José Martins (Sociedade Brasileira de Dermatologia, 2015)
AbstractSporotrichosis is the most common subcutaneous mycosis. It is caused by the dimorphic fungus Sporothrix schenckii, and the infection is usually acquired by traumatic inoculation. We describe a case of sporotrichosis in an uncommon location with an unusual mode of transmission. A 49-year-old female patient who lived in an urban area of Rio de Janeiro presented with involvement of the left ear. No history of contact with soil, plants or animals was elicited. The suspected source of infection was a pair of handmade wooden earrings. The delay in the diagnosis and treatment resulted in higher morbidity, unsightly scarring and loss of ear lobe.